2022
DOI: 10.3389/fonc.2022.1001807
|View full text |Cite
|
Sign up to set email alerts
|

Global landscape of 2-hydroxyisobutyrylation in human pancreatic cancer

Abstract: As a new type of post-translational modification (PTM), lysine 2-hydroxyisobutyrylation (Khib) was firstly identified in histones and functioned as a regulator of transactivation in mammals. However, the role of Khib proteins remains to be investigated. Here, we firstly identified 10,367 Khib sites on 2,325 modified proteins in seven patients with pancreatic cancer by applying liquid chromatography with tandem mass spectrometry (LC-MS/MS) qualitative proteomics techniques. Among them, 27 Khib-modified sites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Additionally, Kcr and Khib modifications were also verified to contribute to gastrointestinal cancer metastasis, with elevated ENO1 Kcr in human CRC tissues promoting CRC cell invasion, migration, and growth by increasing ENO1 activity and upregulating tumor-associated expression [ 152 ]. Inhibiting Khib using MG149, a selective Tip60 inhibitor, significantly reduced the invasion, migration, and proliferation of PC cells [ 153 ].…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%
“…Additionally, Kcr and Khib modifications were also verified to contribute to gastrointestinal cancer metastasis, with elevated ENO1 Kcr in human CRC tissues promoting CRC cell invasion, migration, and growth by increasing ENO1 activity and upregulating tumor-associated expression [ 152 ]. Inhibiting Khib using MG149, a selective Tip60 inhibitor, significantly reduced the invasion, migration, and proliferation of PC cells [ 153 ].…”
Section: Roles Of Novel Acylations In Tumor Metastasesmentioning
confidence: 99%
“… 565 Khib is widely distributed in PC, and treatment with the TIP60 inhibitor MG149 can significantly reduce the total Khib level in PC, which leads to the inhibition of PC cell proliferation, migration, and invasion. 498 Kcr is also involved in cancer regulation, with decreased levels observed in liver, gastric, and kidney cancers and increased levels in thyroid, esophageal, and PC. 566 In addition, p300‐mediated crotonylation enhances the expression of HNRNPA1, promoting HeLa cell malignancies.…”
Section: Other Scfa Modificationsmentioning
confidence: 99%
“…Lower levels of the mitochondrial protein GCDH result in Kglu of the TF NRF2, leading to cell death, indicating that GCDH pathway inhibition is a potential therapeutic strategy for melanoma treatment 565 . Khib is widely distributed in PC, and treatment with the TIP60 inhibitor MG149 can significantly reduce the total Khib level in PC, which leads to the inhibition of PC cell proliferation, migration, and invasion 498 . Kcr is also involved in cancer regulation, with decreased levels observed in liver, gastric, and kidney cancers and increased levels in thyroid, esophageal, and PC 566 .…”
Section: Other Scfa Modificationsmentioning
confidence: 99%
“…Pancreatic cancer Suppression of Khib levels inhibits proliferation, migration, and invasion of PC cells [47] Khib (↑)…”
Section: -Hydroxyisobutyrylation Total Protein Khib (↑)mentioning
confidence: 99%
“…MG149, a highly selective inhibitor of TIP60, markedly decreases total Khib levels in PC, and strongly inhibits PC cell proliferation and invasion [47]. Moon et al have shown that MG149 enhances the efficacy of sorafenib in advanced HCC, probably through upregulating cytotoxic endoplasmic reticulum stress [138].…”
Section: Mystsmentioning
confidence: 99%